A Rhetorical Comparative Study of Kathmandu- Terai/Madhesh Expressway Through Media - Karna, Manoj Kumar (Patan Prospective Journal, 2022)
Nepal Army is a committed institution. Its involvement in constructing Kathmandu-Terai/Madhesh Expressway or, Fast-track (K-TME/KTFT) is from 2011 A. D. but still this fast track progresses just 16.10 percent of the total work, which is quite unbelievable. This article discusses different obstacles of the national pride and other projects which the army is also facing in the fast track work. Keeping in mind the rhetorical theory and ethics, this article has abundant media concerns for comparative studies, the textual study through different texts, and the accidental partly but unofficial fast track visit of the author so, a quasi-experimental method works here. To make army, the government, involved companies and the people realize their common goals towards the fast track among many hurdles, and to act accordingly with high degree of morality, which their language hear, the army will accomplish the work in time and there will be overall benefits.